The effects of Ramadan fasting on various physiological and biochemical parameters on muslim soccer players - Fenni, Y.; Ikiouane, M.; Redjal, M.; Remini, H.; Allam, A.; Zaabar, S. (Apunts Sports Medicine, 2025)
This systematic review aimed to examine the effects of Ramadan fasting on biomarkers and performance in Muslim soccer players, addressing the challenges they face due to disrupted dietary patterns and daily routines during this period. A comprehensive literature search was conducted using electronic databases, following PRISMA guidelines. Studies focusing on Ramadan fasting's impact on soccer players' biomarkers and performance were included and critically evaluated. The study revealed that Ramadan fasting did not negatively impact recovery after matches. However, it resulted in decreases in certain blood parameters and performance indicators. Increased sleepiness and muscle fatigue were also observed. Notably, maintaining a training program during Ramadan did not increase oxidative stress. Fasting improved systemic inflammation biomarkers in obese males and did not adversely affect liver and renal function biomarkers. The effects on body weight and plasma volume appeared to be linked to dietary factors or the body's biochemical response to fasting. While Ramadan fasting presents challenges for Muslim soccer players, its overall impact on performance and recovery appears manageable. The findings suggest that players can maintain their performance levels during Ramadan with proper management and training adjustments. However, individual variations and specific aspects of performance should be considered when developing strategies for Muslim athletes during this period.